Erosive tooth wear and caries experience in children and adolescents with obesity. (April 2019) - Tschammler, Claudia; Simon, Alexandra; Brockmann, Knut; Röbl, Markus; Wiegand, Annette
Abstract: Clinical Significance: A large consumption of fermentable carbohydrates, for instance the high intake of sweetened beverages, is an important risk factor for overweight and obesity. As lemonades and fruit juices present high sugar content and quite low pH-values, overweight and obese children might also have an increased risk for dental caries and erosive tooth wear. Objectives: The aim was to analyze the prevalence and severity of erosive tooth wear and caries experience in children and adolescents with overweight, obesity and extreme obesity compared to children with normal weight and to determine a possible association between erosive tooth wear and caries experience. Methods: 223 children (4–17 years, n = 1476 primary and n = 4110 permanent teeth) were examined using standardized dental indices (BEWE, ICDAS, DMFT). Demographic and socio-economic data, eating habits, oral hygiene, fluoride supply and details of medical history were obtained from a questionnaire. Weight classification was based on age- and gender-specific relative body mass indices (BMI). Statistical analyses were done by Chi 2 -tests, Kruskal-Wallis tests, logistic and linear regressions. To determine a possible association between erosive tooth wear and caries experience Chi 2 -tests (prevalence to prevalence) and Spearman correlations (severity to severity) were performed (p < 0.05). Results: Erosive tooth wear and caries experience in primary and permanent teeth were significantly increased in children with obesity and extreme obesity compared to normal weight children (p < 0.05). Higher BMI, age, gender, and the consumption of erosive snacks/beverages were identified as statistically significant risk factors for erosive tooth wear. Higher BMI, age, socio-economic factors, poor toothbrushing habits, and consumption of cariogenic beverages were identified as significant caries risk factors. Erosive tooth wear and caries showed a weak correlation in children with (extreme) obesity (Φ = 0.110 to 0.248). Conclusions: Higher BMI of children and adolescents is significantly associated with a higher risk for erosive tooth wear and caries.